A Target-Oriented Data Envelopment Analysis for Energy-Environment Efficiency Improvement in Japan - Soushi Suzuki; Peter Nijkamp; Piet Rietveld (Tinbergen Institute, 2013)
This paper offers a quantitative contribution to energy-environment policy in Japan in the aftermath of the Fukushima nuclear power accident. Since then, nuclear power energy supply has almost entirely been banned .There is no clear-cut direction for energy policy, as each option involves costs and CO2 consequences. A balanced energy-environment policy is difficult to achieve and there is an urgent need for a comprehensive efficiency and performance analysis of the Japanese energy sector. This paper presents a newly developed adjusted DEA model, emerging from a blend of the Euclidian Distance Minimization EDM method and the Target-Oriented (TO) approach based on a Super-Efficiency model, for generating an appropriate efficiency-improving projection model. The TO approach specifies a Target-Efficiency Score (TES) for inefficient DMUs. This approach can compute an input reduction value and an output increase value in order to achieve a higher TES. This model will be applied to an efficiency analysis of the energy-environment interface for ten regions in Japan. The focus is on two input cost criteria (viz. expenditures and CO2 emission) and two output performance criteria (viz. electricity generation and regional CO2 absorption). A comparative performance analysis of the ten Japan regions under consideration will be pursued.
Keywords: L93; 330; Data Envelopment Analysis (DEA); Euclidean Distance Minimisation (EDM); Target-Oriented (TO); Energy-Environment efficiency